Derechos en la Encrucijada: el Trabajo en Plataformas de Reparto en Argentina y Brasil - Del Bono, Andrea; Droppa, Alisson (El Colegio de México, 2024)
This article examines the transformation of work driven by the platform economy, focusing on digital delivery platforms in Argentina and Brazil. Technological innovations have created a legal vacuum and significant labor precarization, especially for those working in delivery applications. The text analyzes the tensions between companies and workers regarding labor regulation and, using a qualitative and exploratory methodology, examines judicial decisions and legislative proposals in both countries, highlighting the lack of consensus in classifying the employment relationship. The findings underscore the importance of advancing regulation that protects workers' rights in the context of the digital economy.